Temporal interference stimulation targeting right frontoparietal areas enhances working memory in healthy individuals - Zhang, Yufeng; Zhou, Zhining; Zhou, Junhong; Qian, Zhenyu; Lü, Jiaojiao; Li, Lu; Liu, Yu (Frontiers in Human Neuroscience, 2022)
Background: Temporal interference (TI) stimulation is a novel technique that enables the non-invasive modulation of deep brain regions. However, the implementation of this technology in humans has not been well-characterized or examined, including its safety and feasibility. Objective: We aimed to examine the feasibility, safety, and blinding of using TI on human participants in this pilot study. Methods: In a randomized, single-blinded, and sham-controlled pilot study, healthy young participants were randomly divided into four groups (TI and transcranial alternating current stimulation (tACS) targeting the right frontoparietal region, TI-sham, and tACS-sham). Each participant was asked to complete N-back (N = 1 to 3) tasks before, during, and after one session of stimulation to assess their working memory (WM). The side effects and blinding efficacy were carefully assessed. The accuracy, reaction time (RT), and inverse efficiency score (IES, reaction time/accuracy) of the N-back tasks were measured. Results: No severe side effects were reported. Only mild-to-moderate side effects were observed in those who received TI, which were similar to those observed in participants receiving tACS. The blinding efficacy was excellent, and there was no correlation between the severity of the reported side-effects and the predicted type of stimulation that the participants received. WM appeared to only be marginally improved by TI compared to tACS-sham, and this improvement was only observed under high-load cognitive tasks. WM seemed to have improved a little in the TI-sham group. However, it was not observed significant differences between TI and TI-sham or TI and tACS in all N-back tests. Conclusion: Our pilot study suggests that TI is a promising technique that can be safely implemented in human participants. Studies are warranted to confirm the findings of this study and to further examine the effects of TI-sham stimulation as well as the effects of TI on deeper brain regions.